Genome-wide distribution of histone H4 Lysine 16 acetylation sites and their relationship to gene expression - Horikoshi, Nobuo (BioMed Central, 2013)
BACKGROUND: Histone post-translational modifications are critical determinants of chromatin structure and function, impacting multiple biological processes including DNA transcription, replication, and repair. The post-translational acetylation of histone H4 at lysine 16 (H4K16ac) was initially identified in association with dosage compensation of the Drosophila male X chromosome. However, in mammalian cells, H4K16ac is not associated with dosage compensation and the genomic distribution of H4K16ac is not precisely known. Therefore, we have mapped the genome-wide H4K16ac distribution in human cells. RESULTS: We performed H4K16ac chromatin immunoprecipitation from human embryonic kidney 293 (HEK293) cells followed by hybridization to whole-genome tiling arrays and identified 25,893 DNA regions (false discovery rate <0.005) with average length of 692 nucleotides. Interestingly, although a majority of H4K16ac sites localized within genes, only a relatively small fraction (~10%) was found near promoters, in contrast to the distribution of the acetyltransferase, MOF, responsible for acetylation at K16 of H4. Using differential gene expression profiling data, 73 genes (> ±1.5-fold) were identified as potential H4K16ac-regulated genes. Seventeen transcription factor-binding sites were significantly associated with H4K16ac occupancy (p < 0.0005). In addition, a consensus 12-nucleotide guanine-rich sequence motif was identified in more than 55% of the H4K16ac peaks. CONCLUSIONS: The results suggest that H4K16 acetylation has a limited effect on transcription regulation in HEK293 cells, whereas H4K16ac has been demonstrated to have critical roles in regulating transcription in mouse embryonic stem cells. Thus, H4K16ac-dependent transcription regulation is likely a cell type specific process.